Greening the financial sector: evidence from bank green bonds - Bedendo, Mascia (Journal of business ethics, 2023)
Banks are expected to play a key role in assisting the real economy with the green transition process. One of the tools used for this purpose is the issuance of green bonds. We analyze the characteristics of banks that issue green bonds to understand: (i) which banks are more likely to resort to these funding instruments, and (ii) if the issuance of green bonds leads to an improvement in a bank's environmental footprint. We find that large banks and banks that had already publicly expressed their support for a green transition are more likely to issue green bonds. Conditional on being a green bond issuer, smaller banks tend to resort to green bonds in a more persistent manner and for relatively larger amounts, while larger banks issue green bonds on a more occasional basis and for smaller amounts. This heterogeneity is also reflected in our findings that only banks that issue green bonds more intensively improve their emissions and reduce lending to polluting sectors, thus contributing to the decarbonization of the financial sector.